Case report: Hysteroscopy combined with a vaginal mold for severe recurrent vaginal adhesion and stenosis with pyocolpos after pelvic fracture in a 13-year-old female - Wang, Jiao; Zheng, Fei; Wang, Dandan; Yang, Qing (Frontiers in Pediatrics, 2022)
Vaginal adhesions and stenosis are infrequent long-term sequelae following pediatric pelvic fractures. Patients may not present with signs and symptoms before menarche, leading to delayed diagnosis and treatment. We report an adolescent girl who presented with a post-abdominal trauma pelvic fracture and urethrovaginal fistula and subsequent severe vaginal adhesion, which resulted in infection and obstructive symptoms after menarche. Hysteroscopy-guided vaginal adhesion release using an epidural catheter and ultrasonography was performed, followed by vaginal dilation, to resolve obstructive symptoms. For girls with pelvic fractures, education on possible long-term sequelae is required, as is regular follow-up. Timely diagnosis and treatment are important, and hysteroscopic release of vaginal adhesion and postoperative regular vaginal dilation may be an effective treatment.